Ways of improvement techniques of the speed development in football players - Synytsya A.V (Kharkov National Pedagogical University, 2010)
The theoretical methodological ground of importance of the use of facilities and methods of speeding up is resulted for footballers on the different stages of preparation. The state-of-the-art review of scientific sources of literature is carried out on the specific of speeding up for footballers. The base aspects of speed are considered. Recommendations are presented in relation to its perfection on the initial stage of preparation. The forms of control of speed capabilities are recommended. Development of speed capabilities is included in the complement of general and special physical preparation of footballers.